Formulation, Optimization, and In vivo Evaluation of Clozapine Loaded Transdermal Drug Delivery System for the Treatment of Schizophrenia - Patel, Mayur M. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The present research work was intended to develop and optimize transdermal matrix patch of clozapine using Box–Behnken experimental design (Box–Behnken design [BBD]) for improved bioavailability as compared to oral formulation. The 3-factor, 3-level BBD was employed to investigate the combined influence of formulation variables on flux, tensile strength (TS), and in vitro drug release. The generated polynomial equation was validated and desirability function was utilized for optimization. Materials and Methods: Optimized formulation evaluated for physicochemical characterization, Fourier transform infrared, differential scanning calorimetry, in vitro drug release, permeability enhancement potential by ex vivo, skin irritation, and in vivo pharmacokinetics and stability studies. Results: The results of the optimized formulation (F15) showed TS of 6.84 ± 0.64 MPa, flux of 104.80 ± 1.39 (μg/h/cm2), and % drug release after 20 h (Q20) of 82.19 ± 1.12% which was stable up to 6 months in accelerated condition. Observed and the predicted values of the responses were found to be in good agreement. Optimized transdermal patch of clozapine found free from skin irritation as per Draize score method. The pharmacokinetic result had shown the bioavailability of clozapine improved about 2.18-fold after transdermal drug delivery when compared with oral marketed formulation. Discussion and Conclusion: The results of the study revealed that the developed transdermal patch of clozapine can be a promising alternative which provides effective management of schizophrenia in terms of improved patient compliance.